The inner form of the derivative word and its onomasiological structure (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The problem of inner form of the derivative word and its onomasiological structure is raised in the article: the kinds of nominations in the aspect of method of the denomination by the inner form are named, the particularity of the formation of onomasiological structure is discovered, the close connection between explored ideas as representatives of classified and cognitive man activity is confirmed.
Keywords: inner form of word; onomasiological structure; derivative word; nominative unit